Case report: Long-lasting SARS-CoV-2 infection with post-COVID-19 condition in two patients with chronic lymphocytic leukemia: The emerging therapeutic role of casirivimab/imdevimab - Ballotta, Laura; Simonetti, Omar; D’Agaro, Pierlanfranco; Segat, Ludovica; Koncan, Raffaella; Martinez-Orellana, Pamela; Dattola, Federica; Orsini, Emanuele; Marcello, Alessandro; Dal Monego, Simeone; Licastro, Danilo; Misin, Andrea; et al. (Frontiers in Oncology, 2022)
Post-coronavirus disease 2019 (post-COVID-19) condition, previously referred to as long COVID, includes a post-acute syndrome defined by the presence of non-specific symptoms occurring usually 3 months from the onset of the acute phase and lasting at least 2 months. Patients with chronic lymphocytic leukemia (CLL) represent a high-risk population for COVID-19. Moreover, the response to SARS-CoV-2 vaccination is often absent or inadequate. The introduction of monoclonal antibodies (mAbs) in the treatment landscape of COVID-19 allowed to reduce hospitalization and mortality in mild–moderate SARS-CoV-2 infection, but limited data are available in hematological patients. We here report the effective use of casirivimab/imdevimab (CI) in the treatment of two CLL patients with persistent infection and post-COVID-19 condition. Full genome sequencing of viral RNA from nasopharyngeal swabs was performed at the time of COVID-19 diagnosis and before the administration of CI. Both patients experienced persistent SARS-CoV-2 infection with no seroconversion for 8 and 7 months, respectively, associated with COVID symptoms. In both cases after the infusion of CI, we observed a rapid negativization of the nasal swabs, the resolution of post-COVID-19 condition, and the development of both the IgG against the trimeric spike protein and the receptor-binding domain (RBD) of the spike protein. The analysis of the viral genome in the period elapsed from the time of COVID-19 diagnosis and the administration of mAbs showed the development of new mutations, especially in the S gene. The genome variations observed during the time suggest a role of persistent SARS-CoV-2 infection as a possible source for the development of viral variants. The effects observed in these two patients appeared strongly related to passive immunity conferred by CI treatment permitting SARS-CoV-2 clearance and resolution of post-COVID-19 condition. On these grounds, passive anti-SARS-CoV-2 antibody treatment may represent as a possible therapeutic option in some patients with persistent SARS-CoV-2 infection.